Accumulation of Environmental Radioactivity on the Surface of a High Arctic Ice Cap (Flade Isblink, NE Greenland) - Beard, Dylan B.; Baccolo, Giovanni; Clason, Caroline C.; Millward, Geoffrey E.; Łokas, Edyta; Di Stefano, Elena; Rangecroft, Sally; Sala, Dariusz; Wachniew, Przemysław; Blake, William H. (Environmental Science & Technology, 2024)
Under climatic warming, glaciers are becoming a secondary source of atmospheric contaminants originally released into the environment decades ago. This phenomenon has been well-documented for glaciers near emission sources. However, less is known about polar ice sheets and ice caps. Radionuclides are one of the contaminants that can be remobilised through ice melting and accumulate in cryoconite material on the surface of glaciers. To understand the cycling of radionuclides in polar glacial contexts, we evaluate the radioactivity of cryoconite samples from Flade Isblink, a High Arctic ice cap in northeast Greenland. The measured radioactivity is among the highest reported across the High Arctic and the highest from Greenland. The high variability observed among the samples is explained by considering the different macroscopic features of single cryoconite deposits. The radioactivity source is compatible with the stratospheric reservoir established during atmospheric nuclear tests and with weapons-grade fissile fuel, likely originating from Novaya Zemlya proving grounds. This study shows that the ability of cryoconite to accumulate radioactivity in remote areas is undisputed, highlighting the need for a deeper understanding of the remobilisation of radioactive species in polar glacial contexts.